A meta-review of methods of measuring and monitoring safety in primary care. (18th August 2021) - O'Connor, Paul; Madden, Caoimhe; O'Dowd, Emily; Byrne, Dara; Lydon, SinÉad
Abstract: Background: A major barrier to safety improvement in primary care is a lack of safety data. The aims of this systematic meta-review (registration: CRD42021224367) were to identify systematic reviews of studies that examine methods of measuring and monitoring safety in primary care; classify the methods of measuring and monitoring safety in the included systematic reviews using the five safety domains of Vincent et al. 's framework and use this information to make recommendations for improving the measurement and monitoring of safety in primary care. Methods: Four databases (Medline, Academic Search Complete, Web of Science and CINAHL) and the grey literature were screened in November 2020, with searches updated in January 2021. Systematic reviews were included if they addressed the measurement of patient safety in primary care and were published in English. Studies were assessed using the Critical Appraisal Skills Programme for systematic reviews. Results: A total of 6904 papers were screened, with 13 systematic reviews included. A commonly reported method of measuring 'past harm' was through patient record review. The most frequent methods for assessing the 'reliability of safety critical processes' were checklists, observations and surveys of staff. Methods used to assess 'sensitivity to operations' included observation, staff surveys, interviews, focus groups, active monitoring and simulated patients. Safety climate surveys were a commonly used as an approach to assess 'anticipation and preparedness'. A number of the reviews concluded that safety data could, and should, be used for 'integration and learning'. The main limitation of the meta-review was that it was of systematic reviews only. Conclusions: Many of the methods for measuring and monitoring safety are readily available, quick to administer, do not require external involvement and are inexpensive. However, there is still a need to improve the psychometric properties of many measures. Researchers must support the development of psychometrically sound safety measures that do not over burden primary care practitioners. Policymakers must consider how primary care practitioners can be supported to implement these measures.